2008
DOI: 10.1084/jem.20062027
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil-derived neurotoxin acts as an alarmin to activate the TLR2–MyD88 signal pathway in dendritic cells and enhances Th2 immune responses

Abstract: Eosinophil-derived neurotoxin (EDN) is an eosinophil granule–derived secretory protein with ribonuclease and antiviral activity. We have previously shown that EDN can induce the migration and maturation of dendritic cells (DCs). Here, we report that EDN can activate myeloid DCs by triggering the Toll-like receptor (TLR)2–myeloid differentiation factor 88 signaling pathway, thus establishing EDN as an endogenous ligand of TLR2. EDN activates TLR2 independently of TLR1 or TLR6. When mice were immunized with oval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
251
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(265 citation statements)
references
References 70 publications
5
251
0
9
Order By: Relevance
“…There are little data, however, to suggest that deficiency in either IL-5 or eosinophils affects the polarization of protective immunity or by extension the outcome of infection, despite that eosinophil-derived mediators can skew dendritic cells to promote type 2 immunity. 83,84 Thus, eosinophils do not appear to be critical for the generation of T helper cell type 2 (Th2) immunity or clearance of T. muris, 85 and blocking IL-5 does not affect H. polygyrus expulsion despite significantly decreasing eosinophil numbers. 86 If anything, eosinophils act positively on the fecundity of H. polygyrus worms.…”
Section: Transmissionmentioning
confidence: 99%
“…There are little data, however, to suggest that deficiency in either IL-5 or eosinophils affects the polarization of protective immunity or by extension the outcome of infection, despite that eosinophil-derived mediators can skew dendritic cells to promote type 2 immunity. 83,84 Thus, eosinophils do not appear to be critical for the generation of T helper cell type 2 (Th2) immunity or clearance of T. muris, 85 and blocking IL-5 does not affect H. polygyrus expulsion despite significantly decreasing eosinophil numbers. 86 If anything, eosinophils act positively on the fecundity of H. polygyrus worms.…”
Section: Transmissionmentioning
confidence: 99%
“…In this respect, cathelicidins exert their chemotactic activity via FPR-like 1 [11], and they activate APC via P2X7 [60] or EGFR [61]. Eosinophil-derived neurotoxin exerts its chemotactic activity via GiPCR [62], whereas APC are activated via TLR2 [63].…”
Section: Azurocidin Mediates Its Effects On Leukocytes Via ␤ 2 -Integmentioning
confidence: 99%
“…Our data showed that, neurotoxin, some fungal lysates and LPS from the mucosal pathogen Porphyromonas gingivalis bias immune responses towards Th2. [31][32][33][34][35] As there is evidence that TLR synergy can enhance immune responses, [36][37][38][39] the inclusion in a vaccine of multiple TLR agonists may prove highly beneficial. However, the extent to which TLR stimulation, especially that induced by combined TLR agonists, influences immunological potency and the overall Th1/Th2 balance of the immune response is largely unknown.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%